Association of the variants in the PPARG gene and serum lipid levels: a meta‐analysis of 74 studies. Issue 1 (30th September 2014) - Li, Qing; Chen, Rong; Bie, Lizhan; Zhao, Dandan; Huang, Chunkai; Hong, Jiang
Abstract Considerable studies have been carried out to investigate the relationship between the polymorphisms of PPARG (Pro12Ala, C161T and C1431T) and serum lipid levels, but the results were inconclusive. Hence, we conducted a meta‐analysis to clarify the association. MEDLINE, EMBASE and the Cochrane Library databases were searched systematically. The subgroup analysis was performed based on ethnicity. Seventy‐four studies with 54, 953 subjects were included in this meta‐analysis. In Pro12Ala, the group with the 'PP' (C/C genotype) genotype group had lower levels of total cholesterol (TC) (mean difference, MD: −0.02, P < 0.00001; I2 = 28%), low‐density lipoprotein cholesterol (LDL‐C) (MD: −0.02, P < 0.00001; I2 = 30%) and higher levels of triglyceride (TG) (MD: 0.06, P < 0.00001; I2 = 30%) than the combined 'PA+AA' (PA = C/G genotype, AA = G/G genotype) genotype group in Asian population, and the group with the 'PP' genotype had higher levels of TG (MD: 0.07, P < 0.02; I2 = 67%) than the combined 'PA+AA' genotype group in non‐Asian population. No statistically significant differences in the levels of TC, TG, high‐density lipoprotein cholesterol, LDL‐C were detected between different genotypes in C161T(Asian or non‐Asian) and C1431T(Asian) polymorphisms. This meta‐analysis was a renewed and confirmed study to assess the association between PPARG polymorphisms and serum lipid levels in Asian and non‐Asian populations. There is a prominent association between Pro12Ala polymorphism and the levels of TC, LDL‐C and TG in Asian population. No statistically significant differences in serum lipid levels were detected between different genotypes in C161T and C1431T polymorphisms.